2021
DOI: 10.21203/rs.3.rs-258821/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling Osteoclast Defect and Altered Hematopoietic Stem Cell Niche in Osteopetrosis with Patient-Derived iPSCs

Abstract: Background Patients with osteopetrosis present with defective bone resorption caused by the lack of osteoclast activity and hematopoietic alterations, but their bone marrow hematopoietic stem/progenitor cell and osteoclast contents might be different. Osteoclasts recently have been described as the main regulators of HSCs niche, however, their exact role remains controversial due to the use of different models and conditions. Investigation of their role in hematopoietic stem cell niche formation and maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Another indirect mechanism of hematopoietic regulation by osteoclasts is by modulating osteoblast differentiation [138]. It has been suggested that osteoclasts form an HSC niche, based on observations from a mouse model where mice depleted in osteoclasts developed osteopetrosis that caused extramedullary hematopoiesis [138][139][140].…”
Section: Osteoclastsmentioning
confidence: 99%
“…Another indirect mechanism of hematopoietic regulation by osteoclasts is by modulating osteoblast differentiation [138]. It has been suggested that osteoclasts form an HSC niche, based on observations from a mouse model where mice depleted in osteoclasts developed osteopetrosis that caused extramedullary hematopoiesis [138][139][140].…”
Section: Osteoclastsmentioning
confidence: 99%